Colonization and survival capacities underlying the multifaceted life of Rhodococcus sp. PBTS1 and PBTS2. (16th November 2020) - Vereecke, Danny; Fichtner, Elizabeth J.; Lambert, Paul Q.; Cooke, Peter; Kilcrease, James; Stamler, Rio A.; Zhang, Yucheng; Francis, Isolde M.; Randall, Jennifer J.
Abstract: Little is known about the epidemiology of the newly emerged disease on pistachio rootstock designated pistachio bushy top syndrome (PBTS). Here, we analysed the survival and colonization capacities of the two causative agents, Rhodococcus corynebacterioides ‐like PBTS1 and R . fascians PBTS2, in the different habitats they occupy. Additionally, we examined their chromosomal sequences for genes that would support their ecology and provide experimental evidence for some of their predicted functions. We demonstrate that the soil competence of PBTS2 is better than that of PBTS1 and that both bacteria behave chemotactically, allowing them to translocate from soil to the rhizoplane. Once on the rhizoplane and the phylloplane, the PBTS bacteria form extensive epiphytic biofilms, probably aided by exopolysaccharide production. From these biofilms, the bacteria colonize the plant's interior tissues through the formation of ingression sites, likely created by the localized activity of cell wall‐degrading enzymes. The observed systemic spreading of the PBTS strains throughout the plant tissues is probably mediated by surface motility and agrees with the occurrence of symptoms in both the aerial and root parts of the plant host. Based on all available information, we provide a working model on this pathosystem to be used as a conceptual framework for future research. Abstract : Development of a conceptual model on the ecology and mode of action of Rhodococcus sp. PBTS1 and PBTS2, causative agents of pistachio bushy top syndrome, based on functional genomics and microscopy.